Use of the AppsGeyser application in the assessment of self-study activities in English for the equality education - Setyowati, Nining (Journal of Community Service and Empowerment, 2020)
Learning English as a subject that is taught independently to citizens learning non-formal education is one of the most important things to face the challenges of the future and global life, as targeted in SDGs-goal 4. One of the innovative learning strategies that support learning English independently is the use of internet applications. AppsGeyser application is an internet application that allows users to use it offline. With this application we can easily distribute content from websites, blogs and certain files that we want to share via the Android application. The use of android in the process of learning English activities independently. The purpose of writing this real work is to describe and explain the use of the AppsGeyser application in self-study activities in the English language equivalency education package C. The method used in this real work is quantitative descriptive. The population used was all citizens learning the chasing equivalence education package C in PKBM Ilmu Barokah, totaling 10 citizens learning from grade 3. The instruments used in obtaining data were in the form of pretest and posttest with percentage data analysis techniques. The results achieved by learning citizens after using the AppsGeyser application as a learning medium, namely learning citizens become easier to do, enthusiastic in doing quizzes, easier to remember material so that they can answer quizzes smoothly, are more independent in studying learning materials and the results of evaluation of learning citizens increase compared to before using the app.